2020
DOI: 10.1038/s41598-020-70142-7
|View full text |Cite
|
Sign up to set email alerts
|

ATIP3 deficiency facilitates intracellular accumulation of paclitaxel to reduce cancer cell migration and lymph node metastasis in breast cancer patients

Abstract: Taxane-based chemotherapy is frequently used in neoadjuvant treatment of breast cancer patients to reduce tumor growth and lymph node metastasis. However, few patients benefit from chemotherapy and predictive biomarkers of chemoresistance are needed. The microtubule-associated protein ATIP3 has recently been identified as a predictive biomarker whose low levels in breast tumors are associated with increased sensitivity to chemotherapy. In this study, we investigated whether ATIP3 deficiency may impact the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…Previous studies have shown that the expression of MTUS1 is correlated with different cell phenotypes, such as proliferation, differentiation, apoptosis, and ubiquitination, and is a prognostic indicator for multiple cancers. MTUS1 can also regulate cell division by disturbing the microtubule cytoskeleton and can also be used to predict the treatment response to paclitaxel-based chemotherapy in breast cancer [ 21 23 ]. In lung adenocarcinoma tissues, low MTUS1 expression is related to various clinical-pathological parameters, such as tumour size, Ki-67 proliferation index, lymphovascular invasion, and lymph node metastasis, which lead to the correspondingly poor prognosis of patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the expression of MTUS1 is correlated with different cell phenotypes, such as proliferation, differentiation, apoptosis, and ubiquitination, and is a prognostic indicator for multiple cancers. MTUS1 can also regulate cell division by disturbing the microtubule cytoskeleton and can also be used to predict the treatment response to paclitaxel-based chemotherapy in breast cancer [ 21 23 ]. In lung adenocarcinoma tissues, low MTUS1 expression is related to various clinical-pathological parameters, such as tumour size, Ki-67 proliferation index, lymphovascular invasion, and lymph node metastasis, which lead to the correspondingly poor prognosis of patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low expression levels of MTUS1 were significantly correlated with worse OS and DSS, which indicated that these patients had a trend of high survival risk. Logistic regression showed that the expression of MTUS1 in CRC was associated with advanced pathological stages and N stages, suggesting that MTUS1 is important for tumour invasion and lymph node MTUS1 can also regulate cell division by disturbing the microtubule cytoskeleton and can also be used to predict the treatment response to paclitaxel-based chemotherapy in breast cancer [21][22][23]. In lung adenocarcinoma tissues, low MTUS1 expression is related to various clinical-pathological parameters, such as tumour size, Ki-67 proliferation index, lymphovascular invasion, and lymph node metastasis, which lead to the correspondingly poor prognosis of patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the mRNA expression level MTUS1 correlated with cell phenotypes such as cell proliferation, differentiation, apoptosis and ubiquitination and can serve as a prognostic indicator for multiple cancers. MTUS1 can regulates the process of cell division through disturbing microtubule cytoskeleton and has also demonstrated utility to predict treatment response to paclitaxelbased chemotherapy in breast cancer (21)(22)(23). In lung adenocarcinoma tissues, low MTUS1 expression is related to various clinical pathological parameters such as tumor size, Ki-67 proliferation index, lymphovascular invasion and lymph node metastasis, which leads to a correspondingly poor prognosis of patients (14).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ATIP3 expression was significantly down-regulated in taxane-sensitive tumors achieving pathological complete response to chemotherapy [ 58 ], including in the BL1 subtype of TNBC [ 77 ]. Lymph node metastases were also significantly less frequent among low-ATIP3 expressing tumors following treatment with paclitaxel, compared with high-ATIP3 tumors [ 78 ]. These results were rather unexpected as ATIP3 deficiency is associated with increased microtubule dynamics [ 21 ], which is opposite to the microtubule-stabilizing effect of taxanes.…”
Section: Atip3 Is a Predictive Biomarker Of Taxane-based Chemotherapy In Breast Cancermentioning
confidence: 99%
“…At the molecular level, ATIP3 depletion leads to increased accumulation of paclitaxel along the microtubule lattice [ 78 ], which accounts for higher sensitivity to low doses of chemotherapy. These results are consistent with in vitro findings that microtubule instability at the plus ends may improve Taxol binding to microtubules [ 79 ].…”
Section: Atip3 Is a Predictive Biomarker Of Taxane-based Chemotherapy In Breast Cancermentioning
confidence: 99%